Secondary-Atom-Doping Enables Robust Fe–N–C Single-Atom Catalysts with Enhanced Oxygen Reduction Reaction - Luo, Xin (Nanomicro Lett, 2020)
Single-atom catalysts (SACs) with nitrogen-coordinated nonprecious metal sites have exhibited inimitable advantages in electrocatalysis. However, a large room for improving their activity and durability remains. Herein, we construct atomically dispersed Fe sites in N-doped carbon supports by secondary-atom-doped strategy. Upon the secondary doping, the density and coordination environment of active sites can be efficiently tuned, enabling the simultaneous improvement in the number and reactivity of the active site. Besides, structure optimizations in terms of the enlarged surface area and improved hydrophilicity can be achieved simultaneously. Due to the beneficial microstructure and abundant highly active FeN(5) moieties resulting from the secondary doping, the resultant catalyst exhibits an admirable half-wave potential of 0.81 V versus 0.83 V for Pt/C and much better stability than Pt/C in acidic media. This work would offer a general strategy for the design and preparation of highly active SACs for electrochemical energy devices. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40820-020-00502-5) contains supplementary material, which is available to authorized users.